2015
DOI: 10.1371/journal.pone.0136136
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Inadvertent Intraoperative Hypothermia and Its Risk Factors in Patients Undergoing General Anesthesia in Beijing: A Prospective Regional Survey

Abstract: Background/ObjectiveInadvertent intraoperative hypothermia (core temperature <360 C) is a recognized risk in surgery and has adverse consequences. However, no data about this complication in China are available. Our study aimed to determine the incidence of inadvertent intraoperative hypothermia and its associated risk factors in a sample of Chinese patients.MethodsWe conducted a regional cross-sectional survey in Beijing from August through December, 2013. Eight hundred thirty patients who underwent various o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
98
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 38 publications
15
98
1
4
Order By: Relevance
“…These results are in agreement with those previously reported in surgical patients, for whom baseline temperature prior to anesthesia and temperature at the start of the operation were among the most important factors associated with intraoperative hypothermia. 23,24 Hence, reducing the normal core-toperipheral tissue temperature gradient by warming such patients before induction of anesthesia (active prewarming) would be particularly important in this setting to minimize the consequent redistribution hypothermia. Thus, several studies reported that starting active prewarming with warmed intravenous fluid and / or forced-air warming at least 15 min prior to induction of anesthesia and surgical incision was effective for preventing hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with those previously reported in surgical patients, for whom baseline temperature prior to anesthesia and temperature at the start of the operation were among the most important factors associated with intraoperative hypothermia. 23,24 Hence, reducing the normal core-toperipheral tissue temperature gradient by warming such patients before induction of anesthesia (active prewarming) would be particularly important in this setting to minimize the consequent redistribution hypothermia. Thus, several studies reported that starting active prewarming with warmed intravenous fluid and / or forced-air warming at least 15 min prior to induction of anesthesia and surgical incision was effective for preventing hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al previously reported that an infusion of more than one litre of unwarmed fluid tripled the risk of intraoperative hypothermia during surgical procedures performed under general anesthesia. 23 During CD, intravenous fluid coloading is advocated at the time of spinal anesthesia, in combination with infusion of vasopressors, to prevent maternal hypotension. 28 Hence, women may receive 1-3 L of crystalloid fluids intraoperatively and, consequently, may be significantly cooled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shivering is an unpleasant condition which usually occur as a complication after both general and regional anaesthesia in patient underwent either elective or emergency surgery. 1,2, 3 Post-surgical shivering may cause several unwanted complications such as physiological stress, increased oxygen demand by 2-3 times, increased metabolism, increased intracranial and intraocular pressure, elevating carbondioxide production, cathecolamine release, and increased post surgical pain. 4,5, 6 Temperature control at recovery room can be done by using dry blanket to reduce heat evaporation, and the use of warm saline solution.…”
Section: Introductionmentioning
confidence: 99%
“…4 The concern with the development of intraoperative hypothermia exists especially in patients undergoing major surgery, which require long periods of anesthesia. 5 Complications of hypothermia in the intraoperative period that are highlighted by the literature include: coagulopathy and increased need for blood transfusion, morbid coronary events such as heart attack, tachycardia and hypertension, surgical site infection, thermal discomfort, tremors, decreased drug metabolism, and prolonged recovery. Due to the serious consequences associated with hypothermia, the standard of care is to monitor the body temperature during the anesthesia, and maintain a stable temperature.…”
Section: Introductionmentioning
confidence: 99%